2016
DOI: 10.1038/srep24176
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of functional trait diversity among Indian cultivated and weedy rice populations

Abstract: Weedy rice, a menace in rice growing areas globally, is biosimilar having attributes similar to cultivated and wild rice, and therefore is difficult to manage. A study was initiated to characterize the functional traits of 76 weedy rice populations and commonly grown rice cultivars from different agro-climatic zones for nine morphological, five physiological, and three phenological parameters in a field experiment under an augmented block design. Comparison between weedy and cultivated rice revealed a differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…According to one estimate, DSR is practiced in about 15% of rice-planting areas in China (Yao 2012). It is thought that 3 million hectares of Chinese rice fields have been infested with weedy rice, leading to a yield loss of about 3.4 million tonnes per year (Rathore et al 2016). Sun et al (2013) reported that weedy rice has infested approximately 600,000 ha of rice-growing fields in Northeast China.…”
Section: Introductionmentioning
confidence: 99%
“…According to one estimate, DSR is practiced in about 15% of rice-planting areas in China (Yao 2012). It is thought that 3 million hectares of Chinese rice fields have been infested with weedy rice, leading to a yield loss of about 3.4 million tonnes per year (Rathore et al 2016). Sun et al (2013) reported that weedy rice has infested approximately 600,000 ha of rice-growing fields in Northeast China.…”
Section: Introductionmentioning
confidence: 99%
“…The present study revealed significant variations in different traits among the weedy rice accessions and Swarna rice. Other studies on diversity of Indian weedy rice populations suggested that notable variations amongst the functional traits of weedy rices and that morphotypes do not distribute based on agro-climatic zones (Rathore et al, 2016). This manuscript highlights the extent of Swarna yield penalty when competing with weedy rice.…”
Section: Discussionmentioning
confidence: 70%
“…An alternative and efficient strategy would be exploiting the photosynthetic variations within rice system itself, including cultivated and wild rice. There had been a few studies highlighting the photosynthetic differences within cultivated, and among cultivated and wild rice accessions (Kiran et al ., 2013; Kondamudi et al ., 2016; Rathore et al ., 2016; Haritha et al ., 2017; Sung et al ., 2017). In this study, we not only quantified leaf photosynthetic differences across cultivated and wild rice accessions, but also identified the underlying anatomical, biochemical, and photochemical traits mediating higher leaf photosynthesis in rice.…”
Section: Discussionmentioning
confidence: 99%